Funding Social Innovation in Canada: A Conversation with Stephen Huddart and Chad Lubelsky of the McConnell Foundation - Peacock, David; Huddart, Stephen; Lubelsky, Chad (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
Co-editor of this issue David Peacock interviews Stephen Huddart (President and CEO) and Chad Lubelsky (Program Director) of the McConnell Foundation, a historic supporter of postsecondary education across Canada. McConnell’s investments in community service-learning, social entrepreneurial and innovation activities and social infrastructure programs and dialogues have made them a significant partner for many Canadian higher education institutions. Yet not all community-campus engagement scholars and practitioners, and Engaged Scholar readers, may have heard McConnell articulate for itself its aims and goals for Canadian higher education and society. This interview canvasses the scope of McConnell’s work and interests in community-campus engagement, and sheds light on the actions of an influential private actor in the postsecondary sector.
Keywords: Canada; Libre accès; McConnell Foundation; Université

Funding Social Innovation in Canada: A Conversation with Stephen Huddart and Chad Lubelsky of the McConnell Foundation - Peacock, David; Huddart, Stephen; Lubelsky, Chad (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
Co-editor of this issue David Peacock interviews Stephen Huddart (President and CEO) and Chad Lubelsky (Program Director) of the McConnell Foundation, a historic supporter of postsecondary education across Canada. McConnell’s investments in community service-learning, social entrepreneurial and innovation activities and social infrastructure programs and dialogues have made them a significant partner for many Canadian higher education institutions. Yet not all community-campus engagement scholars and practitioners, and Engaged Scholar readers, may have heard McConnell articulate for itself its aims and goals for Canadian higher education and society. This interview canvasses the scope of McConnell’s work and interests in community-campus engagement, and sheds light on the actions of an influential private actor in the postsecondary sector.
Keywords: Canada; Libre accès; McConnell Foundation; Université